Propuesta de buenas prácticas ambientales en las dependencias administrativas del Campus Salache para el reconocimiento Ecuatoriano Ambiental. - Alvarez Salazar, Francisco Javier (2022)
This research is based on the application of good environmental practices for Ecuadorian environmental recognition, which provides ecological and business benefits because it allows CAMPUS-SALACHE to develop CP processes that contribute to an environmental improvement for their respective analysis and baseline survey of water consumption, energy, paper, fuel and waste generation. The research project begins with collecting data for the year 2021 to evaluate the matrix found in the ministerial agreement N°140 of the Ministry of Environment of September 21, 2015, published in the Official Register N° 387 of November 4, 2015. They were meeting several objectives, such as completing more than 80% of the total points of the seven criteria established in the self-assessment matrix that applies to the strategic sector, compliance with Good Environmental Practices, and the application of Cleaner Production in the processes. Subsequently, a proposal has been designed to use the internal resources of the CAREN Faculty. The ISO 14001: 2015 Standard was implemented based on the indicators, which allows for promoting strategies to improve the habits of the university community and thus obtain economical, environmental, and social benefits. This document was developed with the approval of the leaders and managers of the different areas of the Technical University of Cotopaxi, which were vital entities to know the deficits generated by the administrative units of the Salache Campus.